2014
DOI: 10.1161/circulationaha.114.010376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Influences on Outcomes in Patients Hospitalized for Acute Pericarditis

Abstract: Background-The clinical profile with regard to sex and the influences on outcomes in patients who have been hospitalized for acute pericarditis is largely uncharacterized. Methods and Results-We studied all patients aged ≥16 years admitted to the hospital because of acute pericarditis (postpericardiotomy and myocardial infarction associated pericarditis were excluded). Data were collected from a Finnish national registry that included data on all cardiovascular admissions (670 409

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
102
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(119 citation statements)
references
References 33 publications
4
102
0
13
Order By: Relevance
“…Furthermore, we observed a significant decline in the proportion of women hospitalized with acute pericarditis. This is consistent with recently reported findings from a Finnish acute pericarditis cohort study where 65% of patients were men and the incidence rate was 2.02 (95% CI 1.82-2.26; p < 0.001) times higher among men than women [14]. These sex-based differences could be related to the anti-inflammatory effects of estrogen and the proinflammatory role of testosterone in the pericardial and myocardial tissue.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, we observed a significant decline in the proportion of women hospitalized with acute pericarditis. This is consistent with recently reported findings from a Finnish acute pericarditis cohort study where 65% of patients were men and the incidence rate was 2.02 (95% CI 1.82-2.26; p < 0.001) times higher among men than women [14]. These sex-based differences could be related to the anti-inflammatory effects of estrogen and the proinflammatory role of testosterone in the pericardial and myocardial tissue.…”
Section: Discussionsupporting
confidence: 91%
“…The overall CFR of 1.8% in our study is comparable to that reported in previous studies [14]. The CFR declined by 33.4% during the study period.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations